Adenosine A2A Receptor Gene Knockout Prevents l-3,4-Dihydroxyphenylalanine-Induced Dyskinesia by Downregulation of Striatal GAD67 in 6-OHDA-Lesioned Parkinson’s Mice - Yin, Su-bing; Zhang, Xiao-guang; Chen, Shuang; Yang, Wen-ting; Zheng, Xia-wei; Zheng, Guo-qing (Frontiers in Neurology, 2017)
L-3,4-dihydroxyphenylalanine (L-DOPA) remains the primary pharmacological agent for the symptomatic treatment of Parkinson’s disease (PD). However, the development of L-DOPA-induced dyskinesia (LID) limits the long-term use of L-DOPA for PD patients. Some data has reported that Adenosine A2AReceptors (A2AR) antagonists prevented LID in animal model of PD. However, the mechanism in which adenosine A2AR blockade alleviates the symptoms of LID has not been fully clarified. Here, we determined to knockout the gene of A2AR and explored the possible underlying mechanisms implicated in development of LID in a mouse model of PD. A2AR gene knockout mice were unilaterally injected into the striatum with6-hydroxydopamine (6-OHDA) in order to damage dopamine neurons on one side of the brain. 6-OHDA-lesioned mice were then injected once daily for 21 days with L-DOPA. Abnormal involuntary movements (AIMs) were evaluated on days 3, 8, 13, and 18 after L-DOPA administration and Real-time PCR and immunohistochemistry for glutamic acid decarboxylase (GAD) 65 and GAD67 were performed. We found that A2AR gene knockout was effective in reducing AIM scores and accompanied with decrease of striatal GAD67, rather than GAD65. These results demonstrated that the possible mechanism involved in alleviation of AIM symptoms by A2ARgene knockoutmight be through reducing the expression of striatal GAD67.